Modulation of Antibody-Mediated Immune Response by Probiotics in Chickens - Haghighi, Hamid R.; Gong, Jianhua; Gyles, Carlton L.; Hayes, M. Anthony; Sanei, Babak; Parvizi, Payvand; Gisavi, Haris; Chambers, James R.; Sharif, Shayan (Clinical and Diagnostic Laboratory Immunology, 2005)
Classifications Services CVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue CVI About CVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy CVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1556-6811 Online ISSN: 1556-679X Copyright © 2014 by the American Society for Microbiology. For an alternate route to CVI .asm.org, visit: CVI